Pengaruh Perubahan Kurikulum Pendidikan Terhadap Motivasi Belajar Siswa - Sulianti, Ani; Hasanah, Uswatuh; Saila, Nurul (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to investigate the impact of curriculum changes on students' learning motivation at the secondary education level. The curriculum is a key element in the education system that can influence the learning process and student achievement. The data collection technique uses qualitative with a literature study approach. The data source used is a literature study, the data analysis technique used is a comparative study of the literature and identifying the impacts of main curriculum changes on student learning motivation, both positive and negative impacts. The research results show that curriculum changes can have varying impacts on student learning motivation. Positive impacts can occur when curriculum changes include refreshing learning materials, a more interactive teaching approach, clear educational goals, fair evaluation, and challenges that are appropriate to students' ability levels.